2021
DOI: 10.23851/mjs.v32i4.1014
|View full text |Cite
|
Sign up to set email alerts
|

Radon Gas Questionnaire for Students of the College of Science, Mustansiriyah University

Abstract: Questionnaires were designed containing questions relating to 222Rn, to know the student’s awareness of the dangers of 222Rn gas. The questionnaire was distributed randomly to 30 students of the fourth stage of both sexes in the departments of the college of science. The survey shows that the 222Rn awareness of fourth-stage students for all departments of the college of science, Mustansiriyah university is scarce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The results of Table (2) showed the efficiency of silver nanoparticles manufactured locally and biologically by the alga Spirogyra (T1) in preventing the fungus from producing aflatoxin B1 on stored wheat grains at all concentrations, all concentrations showed significant differences with the comparison treatment in which the toxin concentration was 88.4ppb, while the concentrations of AFB1 for the treatment (T1) and with concentrations of 1.5,2 and 3 amounted to 6.25ppb, ppb4.11 and ppb 0 respectively, as the HPLC device did not feel any concentration of toxins when Concentration 3 and the percentage of reduction of the concentrations used was 92.92%, 95.35% and 100%, respectively, while the concentrations of AFB1 in the commercial silver treatment (T2) were at the same concentrations of 2.15, 0 and 0 with a reduction rate of 97.56%, 100% and 100%, respectively, this is in agreement with some studies that indicated the efficiency of nanoparticles in AFB1 reduction [25]. Some studies have indicated the ability of nanoparticles to break down toxic chemicals, such as mycotoxins, including aflatoxin B1, as it can be used as an adsorbent [26,27,28], this results agreed with the findings of [29] who reported the efficiency of silver nanoparticles manufactured biologically and locally by fungi, which gave the reduction efficiency of aflatoxin B1 reached 94.61%, 100% and 100% for concentrations 0.2, 0.4 and 0.6, respectively, these results are also consistent with what was reached by [24], which indicated the efficiency of nano-algae in inhibiting the fungus Sclerotinia sclerotiorum, the nano-algae achieved an inhibition rate (18.24%, 74.31%, 100% and 100%) for the concentrations (0.5, 1,2 and 3), respectively, compared with normal algae, which achieved an inhibition rate of 10.00%, 9.41%, 9.41% and 9.41% for the same concentrations, respectively.…”
Section: Testing the Effectiveness Of Locally And Biologically Manufa...supporting
confidence: 91%
See 1 more Smart Citation
“…The results of Table (2) showed the efficiency of silver nanoparticles manufactured locally and biologically by the alga Spirogyra (T1) in preventing the fungus from producing aflatoxin B1 on stored wheat grains at all concentrations, all concentrations showed significant differences with the comparison treatment in which the toxin concentration was 88.4ppb, while the concentrations of AFB1 for the treatment (T1) and with concentrations of 1.5,2 and 3 amounted to 6.25ppb, ppb4.11 and ppb 0 respectively, as the HPLC device did not feel any concentration of toxins when Concentration 3 and the percentage of reduction of the concentrations used was 92.92%, 95.35% and 100%, respectively, while the concentrations of AFB1 in the commercial silver treatment (T2) were at the same concentrations of 2.15, 0 and 0 with a reduction rate of 97.56%, 100% and 100%, respectively, this is in agreement with some studies that indicated the efficiency of nanoparticles in AFB1 reduction [25]. Some studies have indicated the ability of nanoparticles to break down toxic chemicals, such as mycotoxins, including aflatoxin B1, as it can be used as an adsorbent [26,27,28], this results agreed with the findings of [29] who reported the efficiency of silver nanoparticles manufactured biologically and locally by fungi, which gave the reduction efficiency of aflatoxin B1 reached 94.61%, 100% and 100% for concentrations 0.2, 0.4 and 0.6, respectively, these results are also consistent with what was reached by [24], which indicated the efficiency of nano-algae in inhibiting the fungus Sclerotinia sclerotiorum, the nano-algae achieved an inhibition rate (18.24%, 74.31%, 100% and 100%) for the concentrations (0.5, 1,2 and 3), respectively, compared with normal algae, which achieved an inhibition rate of 10.00%, 9.41%, 9.41% and 9.41% for the same concentrations, respectively.…”
Section: Testing the Effectiveness Of Locally And Biologically Manufa...supporting
confidence: 91%
“…The study carried out by [21] indicated that the morphological changes of the fungi that were treated with nano-silver, and this led to a decrease in their ability to produce toxins, and also found effects of nano-silver on spores, which led to swelling and distortions in the spores, it was also found that there were effects of silver nanoparticles on the spores, as it led to swelling and distortions in the spores and a decrease in the number of spores, and this is very important because the reproduction of Aspergillus is mainly associated with the formation of spores. The reason for the resistance of silver nanoparticles to fungi is also due to the fact that silver nanoparticles create chemical and physical stress, which leads to programmed death in fungus cells [22], these results agreed with what was found by [23] which confirmed the high inhibitory efficiency of Ascophyllum nodosum extract on culture media with concentrations of 0.5 and 1% on the fungi Alternaria cucumerinum and Fusarium oxysporum, these results also agreed with the findings of [24], which found that increasing the concentration of the extract of the nano kelp Ascophyllum nodosum led to an increase in the inhibition of the pathogenic fungus Sclerotinia sclerotiorum.…”
Section: Testing the Effectiveness Of Locally And Biologically Manufa...supporting
confidence: 88%
“…Six isolates of Bacillus cereus bacteria were obtained out of 15 samples, after conducting cultural tests, microscopic examinations, and biochemical tests. Table (1) and the figures below show the results of the biochemical tests that were conducted on them, and the results of the initial tests that were conducted on the colonies indicated that they were stained with Gram stain. It turned out that they were all gram-positive bacilli.…”
Section: Resultsmentioning
confidence: 99%
“…Since they are proteins, they possess the characteristics of proteins and are affected by temperature, acids, and strong bases, which leads to Until they break down and change their natural characteristics, enzymes are formed in the protoplasm and move outside to help in certain reactions outside the cell. They are called exoenzyme, while those that work inside the cell are called endoenzyme [1]. For many, the term enzyme is a common phrase.…”
Section: Introductionmentioning
confidence: 99%